Sensitivity of Trichophyton mentagrophytes strains to three imidazole drugs - Lenhart, K; Merkunová, A (Acta Universitatis Palackianae Olomucensis Facultatis Medicae, 1991)
A total of 84 strains of the dermatophyte Trichophyton mentagrophytes were studied for their sensitivity to ketoconazole, miconazole, and clotrimazole. Minimal inhibitory concentration was used for determination of sensitivity. Variability in the sensitivity of strains to the tested imidazole drugs ranged within one to two orders (10(-2)-10(0) micrograms/ml). By means of UV radiation ketoconazole-resistant mutants were prepared: their frequency was 1.3 x 10(-7) mutants per spore and nucleus. A repeated exposition to the mutagen lead to increased resistance. Correlation was also studied between inhibitory effect of ketoconazole on mycelial growth and that on ergosterol biosynthesis but no significant results were obtained.
Keywords: Miconazole; Ketoconazole; klotrimazol; mikonazol; ketokonazol; mikrobiální testy citlivosti; Microbial Sensitivity Tests; Clotrimazole; Trichophyton; Imidazoles; imidazoly